Real-time monitoring of large-diameter caissons - Sheil, B; Royston, R; Byrne, B (Springer, 2018)
Large-diameter open caissons are a widely-adopted solution for deep foundations, underground storage and attenuation tanks, pumping stations, and launch and reception shafts for tunnel boring machines. The sinking process presents a number of challenges including maintaining verticality of the caisson, controlling the rate of sinking, and minimizing soil-structure frictional stresses through the use of lubricating fluids. A bespoke monitoring system has been developed at University of Oxford to provide early warning of adverse responses during the sinking phase (e.g. excessive soil-structure interface friction). The monitoring system was trialled on a recent pilot project in the UK involving the construction of a 32 m internal diameter, 20 m deep reinforced concrete caisson. This paper describes the monitoring system that was developed and its impact on the construction process of the pilot project. Early indications are that real-time feedback of live construction data has a major impact on the efficiency and safety of the construction process.